2013
DOI: 10.1007/s10840-013-9812-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute changes in electromechanical parameters during different pacing configurations using a quadripolar left ventricular lead

Abstract: In CRT patients receiving a quadripolar LV lead, significant variations in electromechanical parameters were observed by changing pacing vector. Individually targeting the optimal pacing site may enhance the acute haemodynamic response to CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Several studies have also shown changes in LV electrical activation with a quadripolar lead. 61,62 The next logical question is whether MSP using multipolar pacing configurations can improve CRT response. To address this important question, we only have preliminary data from small acute studies (Table 1) and this type of pacing should still be considered experimental, with only preliminary results.…”
Section: Multipolar Leads and Cardiac Resynchronization Therapymentioning
confidence: 99%
“…Several studies have also shown changes in LV electrical activation with a quadripolar lead. 61,62 The next logical question is whether MSP using multipolar pacing configurations can improve CRT response. To address this important question, we only have preliminary data from small acute studies (Table 1) and this type of pacing should still be considered experimental, with only preliminary results.…”
Section: Multipolar Leads and Cardiac Resynchronization Therapymentioning
confidence: 99%
“…This is especially true when resynchronization does not just involve apical segments, but also basal and mid-LV portions for a global effect [ 39 ]. Indeed, in CRT patients receiving an LV lead with multiple selectable electrodes (a quadripolar LV lead), the simultaneous recruitment of a wider portion of LV myocardium is associated with an acute electromechanical improvement [ 40 , 41 , 42 ]. However, in ischemic patients, the benefits of CRT on FMR may be limited in those with significant scar burden because the activation site may not be able to contribute to LV contractility.…”
Section: The Rationale Of Crtmentioning
confidence: 99%
“…It may offer the implanter the option of stability and good pacing capture without repositioning the lead at implant or during follow‐up. Finally, it is also conceivable that a better hemodynamic response may be achieved with multipolar leads . Coronary veins typically taper with smaller diameters in the distal or apical regions in comparison to larger diameters in more proximal or mid to basal regions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is also conceivable that a better hemodynamic response may be achieved with multipolar leads. [11][12][13][14][15][16][17] Coronary veins typically taper with smaller diameters in the distal or apical regions in comparison to larger diameters in more proximal or mid to basal regions. Because of the diameter disparity, it is often more difficult to achieve myocardial contact and, therefore, acceptable pacing thresholds in mid-to-basal regions where the best hemodynamic response could be achieved.…”
Section: Introductionmentioning
confidence: 99%